Cognitive distortion among psychiatric patients - Siddika, Ummey Saima; Chowdhury, Kamal Uddin Ahmed (Dhaka University Journal of Biological Sciences, 2015)
The aim of the current study was to identify the level of cognitive distortions among the patients suffering from psychiatric disorder according to age, gender and educational qualification. Cross sectional survey method was followed, using Bangladesh Cognitive Distortion Scale (BCDS, Siddika and Chowdhury, 2013) on 239 patients, suffering from anxiety and depression for assessing cognitive distortion. Among the psychiatric patients 86.2% respondents found to have clinical level of cognitive distortion. Analysis revealed that there is no significant difference in cognitive distortion according to different age groups and gender. But regarding educational qualification, there is significant difference of total score of Bangladesh cognitive distortion scale (p > 0.01) and it is higher among low literate respondents (non institutional to class 5) than high literate. Dhaka Univ. J. Biol. Sci. 24(2): 191-198, 2015 (July)